Investigation of sensitivity of the proprioceptor system of man to the changes of working place parameters - Vanagienė , I.; Lapė , J. (Psichologija, 1980)
Sensitivity thresholds of the proprioceptor system of man were investigated in the case of changes of working place taken as a whole and of its separate elements (table, chair and foot support) heights and angles. The influence of the absolute parameter value, duration of its estimation, subject posture at the time of changing parameters on the threshold value has been determined. The experiments have shown that sensitivity threshold is independent upon the subject sex and is the same for the table, chair and foot support heights - 8±2 mm. Sensitivity threshold for the table angle changes is equal to 90±20 minutes, for the chair angle changes - to 45± 15 minutes, equally for man and women. Recommendations are given for the psycho-physiological investigations of working places.
Keywords: sensitivity of the proprioceptor system; engineering psychology